2009
DOI: 10.2105/ajph.2008.137174
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Nutrition Support for Food-Insecure Patients and Their Dependents Into an HIV Care and Treatment Program in Western Kenya

Abstract: The Academic Model Providing Access to Healthcare (AMPATH) is a partnership between Moi Teaching and Referral Hospital, Moi University School of Medicine, and a consortium of universities led by Indiana University. AMPATH has over 50,000 patients in active care in 17 main clinics around western Kenya. Despite antiretroviral therapy, many patients were not recovering their health because of food insecurity. AMPATH therefore established partnerships with the World Food Program and United States Agency for Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 7 publications
1
55
1
Order By: Relevance
“…To our knowledge, this is the first study to evaluate the experience of food insecurity and its correlates among PLWHA in Kenya. Food insecurity levels in this study among PLWHA were higher than food insecurity levels reported in other parts of sub-Saharan Africa (Knueppel, et al, 2010; Mamlin et al, 2009). Rural areas may have higher levels of food insecurity due to higher levels of poverty, smaller plots of land per family, and poor soil quality (Mamlin, et al, 2009).…”
Section: Discussioncontrasting
confidence: 83%
“…To our knowledge, this is the first study to evaluate the experience of food insecurity and its correlates among PLWHA in Kenya. Food insecurity levels in this study among PLWHA were higher than food insecurity levels reported in other parts of sub-Saharan Africa (Knueppel, et al, 2010; Mamlin et al, 2009). Rural areas may have higher levels of food insecurity due to higher levels of poverty, smaller plots of land per family, and poor soil quality (Mamlin, et al, 2009).…”
Section: Discussioncontrasting
confidence: 83%
“…In addition, since prior studies have mainly been conducted in (semi-) rural populations in developing areas (2, 4, 7, 8) or at-risk-populations such as the homeless or injecting drug users in resource-rich countries (15, 17, 24), this study extends previous work by focusing on FI among more mainstream and mostly urban PLHIV in a resource-limited setting. These findings could be useful for similar populations in other urban setting in South Asia as well.…”
Section: Introductionmentioning
confidence: 76%
“…Although data are limited on the prevalence of food insecurity in resource-limited settings, a recent summary of 67,038 individuals enrolling in HIV care programs at Academic Model Providing Access to Healthcare clinics in western Kenya reported that 33.5% of enrollees were food insecure, with a range from 20% to 50% depending on clinic site [21••]. A Ugandan survey of 144 households, involving primarily HIV-infected women, found that 59% had low dietary diversity and 44% were accessing food aid.…”
Section: Food Insecurity: Definition Measurement and Prevalencementioning
confidence: 99%